Cyber information operations: Cambridge Analytica's challenge to democratic legitimacy. Issue 2 (4th May 2022) - Dowling, Melissa-Ellen
ABSTRACT: In an era of digital governance, liberal democracy is rapidly transforming to leverage new information technologies as well as contend with them. However, the digitisation of democracy is not without vulnerability. Digitisation has enabled non-state information operations actors (IOAs) to interfere with democratic processes at an unprecedented level and jeopardise the legitimacy of democratic decision-making. One of the first IOAs to digitally interfere in elections was Cambridge Analytica. While some commentators have acknowledged the potential harm that Cambridge Analytica posed to democracy, we are yet to fully understand how the quality of legitimacy, as a crucial component of democracy, can be eroded by non-state IOAs' electoral interference. The paper explores the growing digital threat landscape to offer scholars a new way of thinking about political campaigning as a vector of electoral interference and deepen conceptualizations of input legitimacy. Adopting a case-study approach, I apply theories of political legitimacy alongside democratic theory to analyse the ways in which Cambridge Analytica challenged three axioms of liberal democracy pertinent to decision-making – participation, pluralism and enlightened understanding – and provide policy recommendations for mitigating the threat to democratic legitimacy.